INDUCTION OF FERN SPORE GERMINATION - Weinberg, Eric S. (1969)
Light-induced germination of Anemia spores can be inhibited by AMO-1618, a selective inhibitor of gibberellin biosynthesis. The inhibitor has no effect on gibberellin-induced dark germination and its inhibition of light-induced germination can be reversed by supplying gibberellin. Barley-endosperm bioassay of concentrates of medium in which spores are imbibed in light reveals the presence of substances with gibberellin-like activity; assay of medium from dark-imbibed spores does not. Simultaneous exposure of spores to sub-optimal levels of light and gibberellin leads to additivity of effect on germination level. Uptake of labeled gibberellin by spores in light is similar to that in darkness. The implications of these findings for the light-dependent synthesis of a gibberellin-like germination substance are discussed. The bearing of the observations upon understanding the interaction of light and gibberellins in seeds of higher plants is considered.